Methods for Analyzing School Shooter's Written Communication to Predict Warning Behavior - Savelyev A. O. Aleksey Olegovich; Karpova A. Yu. Anna Yurievna; Tretjyakov D. A. Dmitry Andreevich; Maksimova N. G. Nataliya Gennadievna (2024, 2024)
The paper presents the initial results of automated meaningful features identification contained in written communication of known school shooters. An analysis of open data sets was performed to identify characteristic cognitive, emotional, psychological, and behavioral traits. The identified features will allow for the creation of a methodology for identifying violent behavior warning signals in potential school shooters